Farmer Will Allen and the growing table - Martin, Jacqueline Briggs (Readers To Eaters, 2013)
The story of former basketball star and current urban farmer and activist, Will Allen, whose vision of gardening from abandoned urban sites led to a grassroots feeding craze.